The Cosmopolitan Vernacular: Korean Shamans (Mudang) in the Global Spirituality Market - Liora Sarfati (Religions, 2023)
Cosmopolitanism has often been used to discuss religions that had been institutionalized, canonized, and then transmitted globally through premodern cultural flows. In contrast, vernacular religions have maintained their local uniqueness in terms of pantheons, belief systems, practices, and ritual objects—even into the 21st century. This article discusses the cultural and societal conditions that have enabled the vernacular traditions of Korean shamanism (musok) to travel globally in real and virtual worlds. Not all Korean shamans (mudang) work with foreigners, but the four ethnographic case studies that this article examines are cosmopolitan practitioners. They assert that spirits can communicate beyond spoken languages, that mudang clients do not have to be Koreans, and that media depictions are a vehicle for making the practice available to more people in Korea and worldwide. Such international activity has become an easily achievable task in hypermodern conditions. The vernacular is flexible in meaning and usage because institutions do not supervise it and it is often an undocumented oral tradition. Mudang constantly recreate musok practices from their personal interpretation of the religious experience. Thus, when musok goes global, it is reinterpreted and transformed to fit the cultural understandings of the target audiences.